Capturing Essential Physiological Aspects of Interacting Cartilage and Bone Tissue with Osteoarthritis Pathophysiology: A Human Osteochondral Unit‐on‐a‐Chip Model. Issue 8 (9th April 2022) - Tuerlings, Margo; Boone, Ilja; Eslami Amirabadi, Hossein; Vis, Michelle; Suchiman, Eka; van der Linden, Enrike; Hofmann, Sandra; Nelissen, Rob; den Toonder, Jaap; Ramos, Yolande; Meulenbelt, Ingrid
Abstract: Given the multi‐tissue aspects of osteoarthritis (OA) pathophysiology, translation of OA susceptibility genes towards underlying biological mechanism and eventually drug target discovery requires appropriate human in vitro OA models that incorporate both functional bone and cartilage tissue units. Therefore, a microfluidic chip is developed with an integrated fibrous polycaprolactone matrix in which neo‐bone and cartilage are produced, that could serve as a tailored human in vitro disease model of the osteochondral unit of joints. The model enables to evaluate OA‐related environmental perturbations to (individual) tissue units by controlling environmental cues, for example by adding biochemical agents. After establishing the co‐culture in the system, a layer of cartilaginous matrix is deposited in the chondrogenic compartment, while a bone‐like matrix is deposited between the fibers, indicated by both histology and gene expression levels of collagen type 2 and osteopontin, respectively. As proof‐of‐principle, the bone and cartilaginous tissue are exposed to active thyroid hormone, creating an OA disease model. This results in increased expression levels of hypertrophy markers integrin‐binding sialoprotein and alkaline phosphatase in both cartilage and bone, as expected. Altogether, this model could contribute to enhanced translation from OA risk genes towards novel OA therapies. Abstract : A functional human osteochondral unit‐on‐a‐chip model is realized using microfluidic chip technology and in vitro engineered cartilage and bone tissue in interaction. To capture essential disease‐related physiological aspects of osteoarthritis, hypertrophy is introduced in the tissues. The established human osteoarthritis model of interacting cartilage and bone tissue is bound to advance osteoarthritis clinical and biological research.